The effects of lysosomal Ca2+ release on membrane depolarisation and synaptic plasticity in hippocampus - Foster, W (2017)
Intracellular Ca2+ signalling is essential for the control of almost every physiological process, from muscular contraction to synaptic transmission. Intracellular Ca2+ signals can be generated from both extracellular or intracellular Ca2+ stores. Nicotinic acid adenine dinucleotide phosphate (NAADP) is a ubiquitous and important Ca2+ mobilising second messenger. NAADP signalling causes Ca2+ release from intracellular acidic Ca2+ stores. The functional roles of NAADP signalling and acidic store Ca2+ release in the central nervous system are relatively unknown Brailoiu et al. (2009b) showed that NAADP signalling enhances membrane excitability in neurons of the medulla, Padamsey and Emptage (2011) (Unpublished) find similar effects in pyramidal neurons of the hippocampus. I used pharmacological manipulations in combination with electrophysiological techniques and dendritic Ca2+ imaging to explore the effect of NAADP/acidic store signalling on membrane excitability and synaptic plasticity in pyramidal neurons of the hippocampus. I began by using a membrane permeable form of NAADP (NAADP-AM) to show NAADP/acidic store Ca2+ signalling caused membrane depolarisation. I also showed, with intracellular dialysis of Ca2+ mobilising second messengers, NAADP is unique in its ability to directly cause membrane depolarisation. I then identified glutamate, acting via metabotropic glutamate receptor 1 (mGluR1), as an endogenous stimulus that causes NAADP-mediated Ca2+ release and depolarisation. I next elucidated the signalling pathway responsible for mGluR1/NAADP-mediated depolarisation and showed the requirement of acidic store Ca2+ release, and subsequent amplification of this Ca2+ via ryanodine receptors by Ca2+-induced Ca2+ release. The resulting Ca2+ signal caused inhibition of small conductance K+ channels (SK channels) and membrane depolarisation. SK channels are described to facilitate the induction of plasticity in hippocampal synapses by modulation of GluN Ca2+ entry (Ngo-Anh et al., 2005). Finally, I show that the induction of mGluR1-dependent long-term potentiation requires inhibition of the SK channels via NAADP/acidic store Ca2+ signalling. Group 1 mGluRs are implicated in the pathogenesis of neurodevelopmental disorders such as fragile X syndrome. My findings may identify new targets for the treatment of such diseases.